Using Time Series Models to Analyse Road Accident Fatalities (In Holly Karbala for the period (2010-2015 - طلال محمد علي الججاوي; ابتهاج اسماعيل يعقوب (Iraqi Journal for Administrative Sciences, 2024)
This research aims to analyse Road Accident Fatalities In Holly Karbala for the period (2010-2015) using time series technique (Box&Jenkins) method (Identification ,Estimation ,Diagnostic Checking of Model ,Forcasting ) to find the best forcasting model to the number of Road Accident Fatalities in Holly Karbala for the period (2010-2015) .The result of data analysis show that the proper and suitable model is Integrated Autoregressive model ARIMA(0,1,1). According to this model we obtained forcasts of Road Accident Fatalities for the next (10) years in monthly base, so the forcasting data are consistent with the observed one which refers to the efficiency of the model.